Numerical Analysis of the Load-Displacement Behaviour of Cast-in-Place Progressive Anchorage in Reinforced Concrete Members - Matúš Farbák; Jozef Jošt; Richard Hlinka; Miroslav Rosmanit (Applied Sciences, 2021)
Modern construction requirements for building structures are currently focused on reducing the time required for construction, dealing with the lack of qualified human resources and ensuring comprehensive construction work quality. The problems mentioned above of today’s construction industry are significantly reduced by modern prefabrication and the efficient use of the most common building materials—steel and concrete. Critical components of such construction systems are their joints. Currently, there are many different types of joints of precast concrete structural elements. Integral parts of these joints are the various anchorages. For connecting load-bearing components, cast-in-place anchor systems are preferred to post-installed ones. The appropriate design of this small but crucial structural component is a complicated engineering issue in some cases. The finite element method (FEM) represents a practical opportunity to design and analyze anchorage systems in detail. A detailed numerical study based on an experimental program was performed to understand cast-in-place anchors’ real behavior and clarify some of the parameters of their design. This paper explains the creation of a numerical model, compares the FEM model with the performed experiments and presents the interesting results of the performed parametric study.